Cultivable Hydrocarbonoclastic Microbial Community from Historically Polluted Soil: Tests for Consortium Development. Issue 3 (3rd April 2019) - Cocarta, D.M.; Dumitru, D.M.; Pesciaroli, L.; Felli, M.; Raduly, B.; Crognale, S.
ABSTRACT: Contamination of soil by petroleum products is a global concern. Microbial-based bioremediation strategies could be cost-effective alternatives to other remediation methods; however, they should be site-tailored to guarantee effectiveness and success. The present paper illustrates data on autochthonous microbial communities in a hydrocarbon pollute soil, considering not only bacteria, but also yeasts and filamentous fungi as strains with pollutant degradation capability. The interesting strains were identified as members of the genus Pseudomonas, Rhodotorula, Yarrowia, Penicillium and Aspergillus. Preliminary tests for consortium assemblage were carried out to evaluate the selected strains as possible inoculum in biotreatment via autochthonous bioaugmentation (ABA).